1974
DOI: 10.1128/jvi.14.6.1337-1342.1974
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis DNA Polymerase III Is Required for the Replication of the Virulent Bacteriophage φe

Abstract: which is more suitable for studies of DNA synthesis in vitro than the single mutant strain U2355pol IIPs (DNA polymerase III").

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

1975
1975
1990
1990

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Although host DNA polymerase I is apparently not required for SP01 phage development, there is evidence that the bacterial DNA polymerase Ill is necessary for replication of related phage 4e. Thus, mutants of B. subtilis with temperature-sensitive lesions in the pol C gene which directs the synthesis of host polymerase III cannot be productively infected with Oe at the nonpermissive temperature (167). The role of host polymerase II in either host or phage development has not yet been elucidated.…”
Section: Development Of Hmu-containing Phagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although host DNA polymerase I is apparently not required for SP01 phage development, there is evidence that the bacterial DNA polymerase Ill is necessary for replication of related phage 4e. Thus, mutants of B. subtilis with temperature-sensitive lesions in the pol C gene which directs the synthesis of host polymerase III cannot be productively infected with Oe at the nonpermissive temperature (167). The role of host polymerase II in either host or phage development has not yet been elucidated.…”
Section: Development Of Hmu-containing Phagesmentioning
confidence: 99%
“…This result might reasonably be interpreted to mean that host polymerase III is not required for the development of most B. subtilis phages, and it appears to contradict the just-mentioned studies of Lavi and co-workers that indicate this enzyme is essential for replication of Oe DNA, even though development of this phage is resistant to HPUra. The conflict between these findings remains to be resolved although it has been suggested that resistance to the drug, at least in the case of Oe, may be associated with a phage-directed modification of DNA polymerase III which is responsible for a shift to exclusive synthesis of viral DNA and a cessation of host genome replication (166,167).…”
Section: Development Of Hmu-containing Phagesmentioning
confidence: 99%
“…SPOl (45), SPO2c, (39), and qe (19) induce a large increase in DNA polymerase activity, as does PBS2 (31). The SPOl-induced DNA polymerase has been purified and is resistant to reduced HPUra in vitro (46).…”
mentioning
confidence: 99%
“…There is, however, one report contradictory to the idea that host Pol III is not required by phages which have HPUra-resistant replication. Using a temperature-sensitive (ts) Pol III mutant of B. subtilis, strain 2355 polA06 mut-1 (2), Lavi et al (19) showed that phage 4e DNA synthesis does not occur in this mutant at 48°C (the restrictive temperature for the host) but does occur at the nonrestrictive temperature of 37°C. Phage DNA synthesis does occur at both temperatures in the wild-type strain (2344 poLA06) and in a spontaneous temperature-resistant .…”
mentioning
confidence: 99%
See 1 more Smart Citation